EDUKASI MANFAAT DAN POTENSI KOMERSIAL BUNGA TELANG (Clitoria ternatea L.) UNTUK PEMBUATAN TEH HERBAL DAN PEWARNA ALAMI MAKANAN - Benediktus Ege; Floretina Rahayu Esti Wahyuni; Yakobus Bustami (STKIP Persada Khatulistiwa Sintang, 2023)
Most of the people of Belonsat village keep the butterfly pea flower (Clitoria ternatea L.) to decorate their yard. Whereas the butterfly pea flower (Clitoria ternatea L.) has many health benefits and economic potential. This happens because the community has not received education about it. Therefore, an initiative was taken to provide education on the benefits and potential of the butterfly pea flower (Clitoria ternatea L.) in the form of sharing health benefits, training on cultivating in large quantities, keeping the plants flowering quickly, carrying out picking, sorting, drying, and wrapping butterfly pea flower, as well as provide training to manage these business activities. Through the activities that have been carried out, the Belonsat village community has gained knowledge and skills regarding the use of butterfly pea flowers as a basic ingredient for herbal teas and natural food coloring.